Many-objective optimization for construction project scheduling using non-dominated sorting differential evolution algorithm based on reference points - Kaveh, A; Rajabi, F; Mirvalad, S (Scientia Iranica. Transaction A, Civil engineering, 2021)
Scheduling is considered one of the most significant factors in the success of construction projects. In recent years, global construction markets have become increasingly competitive and the number of project stakeholders has grown significantly. As a result, concurrently pursuing multiple project objectives, such as optimizing the time, cost, resources, environmental impact, safety risks, and quality of a project, is imperative. Several types of research efforts have focused on multiple-objective construction scheduling models to deal with the above-mentioned objectives. However, there is still a need to integrate all these objectives in the scheduling process to take into account most aspects of a project. To fill this gap, a many-objective optimization model regarding time, cost, resource, environmental impact, safety, and quality based on a newly developed many-objective optimization algorithm called Non-dominated Sorting Differential Evolution algorithm based on Reference points (NSDE-R) is presented in this study. To determine the most proper schedule based on decision-makers' priorities, the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is merged with the optimization algorithm. The applicability of the proposed model is demonstrated employing a case study of a building construction project.